Preliminary study of gut bacterial abundance in Rhynchophorus ferrugineus (Coleoptera: Dryophthoridae) fed on different diets - Farah Nadiah Rosli; Norefrina Shafinaz Md Nor; Nurul Wahida Othman (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Rhynchophorus ferrugineus or also known as RPW is a major pest in many parts of the world and has infested coconut plantations in Malaysia especially in Terengganu and Kelantan. To date, a combination of many methods such as trapping with pheromone, chemical pesticide, and biological pesticide (Integrated Pest Management) were applied to control RPW infestation. However, IPM often could not be used as a method for total eradication and in addition to that, IPM necessitates continuous laborious effort. Thus, a new target for RPW eradication method with high specificity must be identified. The purpose of this research is to study the effect of different diets towards gut bacterial abundance in RPW and thus widen the knowledge regarding their correlation. Parameter measured were abundance of gut bacteria following different diets treatment. 16S rRNA amplicon sequencing method was used in this research to identify all gut bacteria present in the RPW. Our analysis showed that there are six most abundant group of bacteria with different phylogenetic group rank present in RPW’s gut. This include Enterobacteriaceae, Leminorella grimontii, Entomoplasmatales, Erysipelothrix, Lactobacillus and Leuconostoc. This groups of bacteria were known to have significant roles toward host’s gut such as aiding in digestion, synthesizing hormone, and protecting from pathogenic bacteria growth. Comprehensive data obtained from this study on these microbes have potential to be used in exploring new dimension of RPW pest management.